DELIVERY OF ARTHROGRYPOSIS MULTIPLEX BUFFALO CALF WITH SUPERNUMERARY TOOTH IN THE DENTAL PAD THROUGH PARTIAL FETOTOMY - GHUMAN, SPS; SINGH, N; GANDOTRA, VK (The Indian Journal of Animal Reproduction, 2016)
A buffalo calf suffering from arthrogryposis multiplex and reported for the first time with a supernumerary tooth in dental pad was delivered per-vaginum through single fetotomy cut involving removal of both neck and head.